مصادرِ علمیہ کا اسلامی تصوراور بنیادی مصادرِ شریعہ کا تحقیقی جائزہ: The Islamic Concept of Sources of Knowledge & primary sources of Islamic Shariah; A Research Review - Jan, Dr. Muhammad Tahir; Raza, Muhammad Irfan; Fazail Asrar Ahmad, Fazail Asrar Ahmad (Al-Amīr Research Journal for Islamic Studies, 2024)
The Islamic concept of sources of knowledge forms a foundational framework guiding intellectual pursuits and understanding within Islamic thought. Rooted deeply in the Quran and the Hadith (Prophetic traditions), this concept delineates avenues through which believers acquire knowledge, discern truth, and navigate their worldly and spiritual endeavors. This paper explores the multifaceted nature of these sources, encompassing revelation, reason, tradition, and experience, elucidating their interplay and significance within Islamic epistemology. It examines how these sources inform various fields including theology, law, ethics, and philosophy, shaping the Muslim worldview and approach to knowledge acquisition. Through a comprehensive analysis, this study aims to elucidate the richness and dynamism of the Islamic understanding of sources of knowledge & the Primary sources of Islamic Shariah. Keywords: Islamic, sources of knowledge, Quran, Hadith, revelation, reason, tradition, experience, epistemology, theology, law, ethics, philosophy, Muslim worldview.